EFFECT OF FLAVONE AND ITS MONOHYDROXY DERIVATIVES ON ANIMAL MODELS OF DEPRESSION IN SWISS ALBINO MICE - S, SHANMUGAPRIYAN; S, JAIKUMAR; S, VISWANATHAN; K, PARIMALA; M, RAJESH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: This research was designed to investigate the antidepressant activity of a few structurally related flavones (flavone, 3‑hydroxyflavone, and 7‑hydroxyflavone) and the possible mechanisms involved. Methods: Antidepressant activity was evaluated in mice by subjecting them to forced swim test and tail suspension test. The involvement of adrenergic, serotonergic, nitric oxide (NO), and opioid mechanisms was investigated using suitable interacting chemicals. Results: Flavone, 3‑hydroxyflavone, and 7‑hydroxyflavone exhibited a significant and dose‑dependent reduction in total time of immobility in the forced swim test and tail suspension test. Pre‑treatment with alpha‑methyl‑para‑tyrosine and parachlorophenyl alanine attenuated the reduction in immobility period produced by flavone and its derivatives in forced swim test. Naloxone pre‑treatment partially reversed the effect of flavone while L‑arginine pre‑treatment did not alter their effect. Conclusion: The investigated flavones exhibited promising antidepressant activity in both the animal models of depression. However, the flavone compounds did not alter the motor coordination and ambulatory behavior in the Rotarod and locomotor activity test. The participation of serotonergic, adrenergic, and opioid mechanism in the antidepressant activity of these compounds was elucidated from the results, and the role of NO pathway was excluded.